Laser Measurement of Building Vibration and Displacement - A.J. Bougard; B.R. Ellis (Shock and Vibration)
This paper considers four laser systems used by the Building Research Establishment (BRE) to investigate the behaviour of structures. Lasers enable remote measurements of vibration and displacement to be taken where access to a structure is difficult or where fire, explosion or structural collapse creates a hazardous environment. Each system will be described, and its use illustrated using measurements taken on real structures.